On the spatial structure and time evolution of shamal winds over the Arabian Sea – a case study through numerical modelling. (29th October 2013) - Vinod Kumar, K.; Seemanth, M.; Vethamony, P.; Aboobacker, V. M.
ABSTRACT Shamal events are extra‐tropical weather systems which occur in winter (cold and dry winds) as well as summer (hot and humid winds) with strong northwesterly or northerly winds blowing over the Arabian Peninsula. We have used Weather Research and Forecasting (WRF) model to simulate a major winter shamal event (having duration of 3–5 days), which occurred in 2008 and analysed the spatial structure and time evolution of shamal winds over the Arabian Sea (AS). The study reveals that horizontally, shamal winds extend upto 14°N and bring out significant changes in the atmospheric temperature—longitudinally from Arabian coast to west coast of India; its vertical extension is upto to approximately 8 km near Oman and approximately 3 km near Ratnagiri coast. Along the Arabian coast a temperature drop of 12 °C is observed and along west coast of India a drop of 5 °C. It gets dissipated when northeast monsoon winds dominate. Its speed reduces from 15 m s−1 (Oman coast) to 9 m s−1 (central AS) as it propagates into AS. However, it must be noted that the present work is limited to a case study and hence, the southerly extension of the phenomenon and the associated changes in air temperature should not be considered a climatological reference. The shamal events may influence the wind induced circulation, heat flux and stratification in the AS, and these need to be analysed further.